The Impact of Preinjury Use of Antiplatelet Drugs on Outcomes of Traumatic Brain Injury: A Systematic Review and Meta-Analysis - Cheng, Li; Cui, Gaoliang; Yang, Rong (Frontiers in Neurology, 2022)
Objective: The study aimed to compare outcomes of traumatic brain injury (TBI) in patients on pre-injury antiplatelet drugs vs those, not on any antiplatelet or anticoagulant drugs. Methods: PubMed, Embase, and Google Scholar databases were searched up to 15th May 2021. All cohort studies comparing outcomes of TBI between antiplatelet users vs non-users were included. Results: Twenty studies were included. On comparison of data of 2447 patients on pre-injury antiplatelet drugs with 4814 controls, our analysis revealed no statistically significant difference in early mortality between the two groups (OR: 1.30 95% CI: 0.85, 1.98 I2=80% p=0.23). Meta-analysis of adjusted data also revealed no statistically significant difference in early mortality between antiplatelet users vs controls (OR: 1.24 95% CI: 0.93, 1.65 I2=41% p=0.14). Results were similar for subgroup analysis of aspirin users and clopidogrel users. Data on functional outcomes was scarce and only descriptive analysis could be carried out. For the need for surgical intervention, pooled analysis did not demonstrate any statistically significant difference between the two groups (OR: 1.11 95% CI: 0.83, 1.48 I2=55% p=0.50). Length of hospital stay (LOS) was also not found to be significantly different between antiplatelet users vs non-users (MD: -1.00 95% CI: -2.17, 0.17 I2=97% p=0.09). Conclusion: Our results demonstrate that patients on pre-injury antiplatelet drugs do not have worse early mortality rates as compared to patients, not on any antiplatelet or anticoagulant drugs. The use of antiplatelets is not associated with an increased need for neurosurgical intervention and prolonged LOS.